Ekstraksi Oleoresin Lada Hitam Secara Maserasi Menggunakan Metode Permukaan Respon - Liya Fitriyana; Irmayanti Irmayanti; Putri Meutia Sari; Virna Muhardina (Fakultas Teknik, 2018)
Purpose of this study is to determine the optimum conditions of extraction using conventional methods (maceration) and ultrasonic methods by using response surface method (RSM). The variables used in this study is the ratio of solvent with black pepper, temperature and time of extraction. Solvents used in this study is 99% ethanol. The bigest yield of oleoresin using maceration method was 4.42% with a ratio of solvent and black pepper for 1: 4 g / ml and extraction time of 4.68 hours. GC-MS test showed that the piperine contained in oleoresin extracted by using maceration are respectively69.92% FT-IR test showed that oleoresin extracted using maceration have the same bound that same as piperine bound. Organoleptic test showed that oleoresin produced by using maceration meet the requirement of ISO standards 06-2388-1998 (dark brown color, pepper smell and thick paste form).